Pola Membangun Karakter Anak Melalui Kegiatan Ekstrakurikuler Di RA Ummu Zainab Cikampak - Hanisa, Fildza (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2021)
This article discusses the pattern of building children's character through extracurricular activities at RA Ummu Zainab Cikampak with the aim of knowing the forms of character building of children at RA Ummu Zainab Cikampak, to find out the implementation of building children's character through extracurricular activities at RA Ummu Zainab Cikampak, to find out factors -Factors supporting and inhibiting the development of children's character in RA Ummu Zainab Cikampak. The type of research used in this research is descriptive qualitative research. Based on the results of data collection and processing, the results can be summarized as follows: Forms of child character development through extracurricular activities at RA Ummu Zainab Cikampak are Routine Study Activities. The implication of this research is that principals, teachers, and parents of children pay more attention to the potential and creativity of children and provide support and motivation for children to become a generation of character.